Effect of integrated land management, slope position and land-use type on soil physicochemical properties, discharge, species richness and carbon stock in Geda watershed, north Shewa Ethiopia - Terefe, Hailu (Addis Ababa University, 2020)
Watershed based integrated land management is a recent approach to curb land degradation in Ethiopia and introduced in 2012 in Geda watershed, central highlands of Ethiopia. However, the impacts of the interventions on indicators of some ecosystem services were not assessed. The objectives of this study were to explore the effects of the interventions on soil properties, soil moisture content and water discharge, plant species richness, biomass production and carbon stock by comparing treated site with integrated land management measures and the adjacent untreated site. Samples were collected from treated and untreated sites in the upper and lower slope positions, from cropland, grazing land and Tree Lucerne plantation based on standard procedures for each objective. The collected data were analyzed following standard statistical procedures with respect to treatment, slope position, land-use type, and soil depth. The introduced integrated land management significantly (p ≤ 0.001) improved most of the soil physicochemical properties, the soil moisture content, water discharge, plant species richness, biomass production and carbon stocks. Clay, total N, available P and soil organic carbon were significantly higher at p = 0.001 and exchangeable K at p = 0.05 in the treated site compared to the untreated one. This could be due to higher organic matter accumulation and improved vegetation growth as a result of prohibited free grazing, and reduced erosion by the conservation structures. Sand and bulk density were significantly (p = 0.001) higher in the untreated site that could be attributed to erosion due to absence of conservation measures and compaction by livestock trampling during free grazing practice. Generally, the introduced integrated land management measure improved clay content of the soil by 63.51%, OC by 133%,